Trapeziometacarpal joint arthritis - Patel, Tejas J. (Current Science Inc., 2012)
Trapeziometacarpal (TM) joint arthritis is a common cause of radial-sided wrist pain that preferentially affects women. It is diagnosed by a thorough history, physical examination, and radiographic evaluation. While radiographs are used to determine the stage of disease, treatment is dependent on symptom severity. Nonoperative treatment frequently consists of activity modification, non-steroidal anti-inflammatory drugs (NSAIDs), splinting, and corticosteroid injections. After failure of conservative treatment, various surgical options exist depending on the stage of disease. This article reviews the literature supporting the various surgical treatment options. Special consideration is given to the comparison of trapeziectomy with and without tendon interposition and ligament reconstruction.